BASA BASITA PARIBASA BALI DALAM ALBUM MABALIH WAYANG KARYA KETUT BIMBO - Rahayu Trisnayanti, Komang; Iwan Indrawan Jendra, I Made; Purnomo Arta, Putu Eddy (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Paribasa Bali is speech or words, teachings, reprimands, rebukes, rebukes, lashes or punishments. Paribasa Bali can be used as plastic (decoration) used in conversation or in public relations. Paribasa is also found in Balinese pop songs, such as the one on the album Mabalih wayang by Ketut Bimbo. The formulation in this study is: what are the types of Balinese paribasa that are in the Mabalih wayang expert song album, Ketut Bimbo? This study aims to indicate that the Balinese language tells about the paribasa so that the Balinese paribasa is known by the Balinese people and so that the Balinese paribasa is preserved so that it does not become extinct. The theory used in this research is the stylistic theory. This research is descriptive qualitative. The results showed that according to Simpen there were fourteen paribasa, namely: sesonggan, sesenggakan, wewangsalan, sloka, beladbadan, sesawangan, cacimpedan, cecangkriman, Sisimbing, cecangkitan, raos ngempelin, sipta/sasemon, types of parikan, gegendingan and according to Tinggen paribasa and thirteen paribasa, namely: cecimpedan (riddles), bladbadan (sound play), raos ngempelin (double meaning words), sesawangan (parables), Sisimbing (satire), sloka (thimble), sesenggakan (like), sesongan (proverb), greeting (greetings), wewangsalan (tamsil), peparikan (rhymes), tetingkesan (litotes), sesawen (signs, symbols). However, there are only six types of Balinese paribasa contained in the song Mabalih wayang album by Ketut Bimbo, namely: sesenggakan, wewangsalan, peparikan, sesawangan, cecangkitan and Sisimbing.